The ‘archbishopric’ of Dol and the ecclesiastical politics of ninth-century Brittany - Smith, Julia M. H. (Studies in church history, 1982)
In the history of the invasions which marked the end of the Roman empire in the west, the Armorican peninsula of northwestern Gaul holds a distinctive place. It witnessed the only substantial settlements by people whose homeland lay within the Roman empire, and who had been subject to Roman civil government for several centuries. These settlers crossed the English Channel probably between the late fourth and early seventh centuries. Establishing new communities in the sparsely populated areas of western Armorica, they brought with them their own language, social patterns and Christian organisation, and a strong sense of affinity with the Celts of Wales and Cornwall from whom they derived.’ Whilst the Britons were establishing themselves as Bretons, the Franks were asserting their hold over the remainder of northern Gaul. A few of them settled in the eastern approaches to the peninsula, in the Roman civitates of Rennes and Nantes. Culturally and politically, only this part of Armorica was attached to Merovingian Gaul, having as its kings the descendants of Clovis, and as its bishops members of the Gallo-Roman aristocracy.